Consumer behavior and decision making (Henry Stewart Talks, 2026)
Consumer behavior definition, Influences on consumer behavior, Consumer decision-making stages, Motivations for consumer choices, Social influence and social media, Digital age impact on consumers, Adapting strategies to consumer expectations